T’boli-Bla’an Dream Weaving: compare to Native Amercian The Sonenekuiñaji, The Parintintin, The Chipewyan (A Casale) & E Hill as "meaning construction" & social-spiritual self w/ dreaming as transcendence in divine grace,& guidance w/ divine inspiration + - Charles Peck Jr (2024)
“The craft of weaving among the T’boli is a sacred spiritual tradition. Designs are believed to arrive from Fu Dalu, the spirit of the Abaca [material for cloth] (p.214). T’boli people are known to be one of the most creative and artistic ethnolinguistic group in the Philippines (Cudera et al., 2020). Among the different T’boli art forms, T’nalak is one of the most popular and admired around the globe. T’nalak is a traditional hand-woven cloth indigenous to the T’boli people from the Cotabato region. It is woven in order to celebrate and pay tribute to major life events such as birth, life, marriage, or death within the community. The cloth is woven from abaca fibers and is naturally dyed from bark, roots, and certain plants. The fabric undergoes a unique tie-dye process where it is tied in specific knots measured by finger or knuckle length, and dipped in dyes in order to create ornate patterns that indicate precision in craftsmanship. This is denoted by a distinctive tri-color scheme; the background is painted black while the pattern is white, which is then tinted predominantly with shades of red. However, it is not unusual to see creative variations in such a traditional pattern. The T’nalak reflects core themes that can be used to understand Filipino American studies, including bayanihan and damay, which are examples of strong community partnership as participant or recipient. The whole process of T’nalak weaving, from dyeing to weaving, is descended from generation to generation of maternal relatives that necessitated a community of woven fabrics and traditional plant based-dying in order to sustain the tradition of T’nalak weaving. By creating specific coloration and subsets of T’nalak, it also provides signs of Filipino cultural identity, rank, and status.